Inquiry-based learning and motivation effects on fifth graders’ IPAS achievement - Waldio Manihuruk; Dede Ruslan; Aman Simaremare (Himpunan Pengembang Kurikulum Indonesia, 2025)
Elementary school students' learning outcomes in Integrated Science and Social Studies (IPAS) are still influenced by low learning motivation and the suboptimal application of instructional strategies aligned with student characteristics. Inquiry learning strategies are believed to enhance learning activity and student engagement, yet their effectiveness in the primary education context requires further empirical validation. This study aims to examine the effects of inquiry learning strategies and learning motivation levels on the IPAS learning outcomes of elementary students. The research employed a quasi-experimental method with a 2x2 factorial design. The participants were fifth-grade students at SD Negeri 060959 Belawan, divided into four groups based on combinations of instructional strategies (inquiry and expository) and levels of learning motivation. Data analysis techniques included normality testing, homogeneity testing, and two-way ANOVA. The results revealed no statistically significant difference in IPAS learning outcomes between students taught using inquiry-based and expository strategies. However, a significant difference was found between students with high and low learning motivation. Furthermore, no significant interaction was found between learning strategy and motivation level in influencing learning outcomes. These findings emphasize the importance of strengthening students’ learning motivation and implementing adaptive instructional approaches that respond to the diverse characteristics of learners. Abstrak Hasil belajar Ilmu Pengetahuan Alam dan Sosial (IPAS) peserta didik sekolah dasar masih dipengaruhi oleh rendahnya motivasi belajar dan belum optimalnya pemilihan strategi pembelajaran yang sesuai dengan karakteristik peserta didik. Strategi pembelajaran inkuiri dipercaya dapat meningkatkan aktivitas belajar dan keterlibatan peserta didik secara aktif, namun efektivitasnya masih perlu dibuktikan secara empiris dalam konteks pendidikan dasar. Penelitian ini bertujuan untuk mengkaji pengaruh strategi pembelajaran inkuiri dan tingkat motivasi belajar terhadap hasil belajar IPAS peserta didik sekolah dasar. Metode yang digunakan adalah kuasi eksperimen dengan desain faktorial 2x2. Subjek penelitian adalah peserta didik kelas V SD Negeri 060959 Belawan yang dibagi ke dalam empat kelompok berdasarkan kombinasi strategi pembelajaran (inkuiri dan ekspositori) dan tingkat motivasi belajar. Teknik analisis data yang digunakan meliputi uji normalitas, uji homogenitas, dan ANOVA dua arah. Hasil penelitian menunjukkan bahwa tidak terdapat perbedaan yang signifikan antara strategi inkuiri dan ekspositori terhadap hasil belajar IPAS. Namun, terdapat perbedaan yang signifikan antara peserta didik dengan motivasi belajar tinggi dan rendah. Interaksi antara strategi pembelajaran dan motivasi belajar tidak memberikan pengaruh signifikan. Hasil ini menegaskan pentingnya memperkuat motivasi belajar peserta didik dan menerapkan pendekatan pembelajaran yang adaptif terhadap karakteristik peserta didik. Kata Kunci: hasil belajar; IPAS; motivasi belajar; pembelajaran inkuiri